Case Report: successful treatment of severe bronchiectasis by inhalation of mesenchymal stem cell-derived exosomes - Liu, Yanyi; Xia, Kun; Zhang, Haoxiang; Li, Guangxi (Frontiers in Medicine, 2025)
Bronchiectasis is a chronic respiratory disorder characterized by irreversible airway dilation and recurrent infections, remains a therapeutic challenge. MSCs-exosomes based treatment is a potential treatment for respiratory disease; however, data regarding the efficacy of this novel therapy are currently lacking. We present a case of bronchiectasis treated with inhaled exosomes derived from human umbilical cord mesenchymal stem cells. As demonstrated in this patient, MSCs-exosomes inhalation may provide comprehensive benefits including reversal of hypoxemia, which could potentially result in enhancement of clinical outcomes and quality of life, and reduction in mortality.